Pengaruh Kombinasi TENS Dan Self-Stretching Terhadap Perubahan Nyeri Dan Kemampuan Fungsional Pada Pasien Low Back Pain Myogenic Di Rumah Sakit Eka Husada - Prasetyo, Samuel Vincentius Dani; Halimah, Nurul; Fau, Yohanes Deo; Fariz, Achmad (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2024)
Objective: This study aims to determine the effect of a combination of TENS and self-stretching on changes in pain and functional ability in patients with Myogenic Low Back Pain at Eka Husada Hospital. Methods: This research is quasi-experimental research. With research design, it refers to the pre-test group and post-test control design. Researchers gave a pre-test on pain and functional ability to 30 respondents with myogenic low back pain who would be given treatment. Then the researchers carried out treatment in the form of a combination of Transcutaneous Electrical Nerve Stimulation and Self-stretching. After completing the treatment, the researcher gave a post-test on pain and functional ability. The research population was all low back pain patients with decreased functional ability, totaling 35 patients at Eka Husada Hospital. The research sample was 30 low back pain patients with decreased functional ability at Eka Husada Hospital who met the inclusion and exclusion criteria. Primary data was collected through direct interviews followed by examination. Data analysis used the Wilcoxon test. Results: Based on the analysis, it is known that there is an effect of a combination of Transcutaneous Electrical Nerve Stimulation and Self-stretching on reducing pain and increasing functional ability in conditions of myogenic low back pain at Eka Husada Hospital Conclusion: There is an effect of TENS and self-stretching on reducing pain and improving function in patients with myogenic low back pain.